TOOLKIT FOR STRATEGIC MANAGEMENT OF AGRICULTURAL PRODUCTION DEVELOPMENT BASED ON DIGITAL TECHNOLOGIES, SMART SPECIALISATION AND INTEGRATION PROCESSES WITHIN THE EUROPEAN ECONOMIC AREA - OLISHEVSKA, Anastasiya; KULISH, Damir (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article develops and substantiates an integrated toolkit for the strategic management of agricultural production development in the context of digital transformation, Smart Specialisation (S3), and integration processes within the European Economic Area (EEA). The research is motivated by the large-scale transformation of Ukraine’s agricultural sector driven by EU integration, the accelerating adoption of digital technologies, and the implementation of dual green and digital transitions. Current challenges, including climate shifts, geopolitical uncertainties, and regulatory changes under the Common Agricultural Policy (CAP 2023–2027), necessitate adaptive models of agricultural management that align with European sustainability standards. The proposed framework addresses the lack of a holistic methodological base capable of integrating technological, economic, and institutional factors into a unified system of strategic management. The study builds upon a review of state-of-the-art approaches in Agriculture 4.0, regional S3 strategies, cluster development, and digital data governance, while also considering OECD and FAO reports, EU regulatory frameworks, and thematic S3 platforms. Methodologically, the toolkit combines strategic foresight and analytics (PESTLE, TOWS, dynamic panels, spatial econometric models), portfolio-based decision-making (GE/McKinsey matrix, real options), and efficiency assessments (DEA, productivity indices). A strong emphasis is placed on data governance, interoperability standards, and monitoring through Balanced Scorecards (BSC) and Key Performance Indicators (KPIs).The novelty of the study lies in the development of the Data–S3–Integration concept, which unifies digital technologies (IoT/IIoT, precision farming, AI/ML, digital twins, blockchain for traceability, satellite monitoring), Smart Specialisation mechanisms, and EU integration instruments into a coherent management model. An implementation roadmap and a system of indicators are proposed for application at firm, cluster, and regional levels, ensuring adaptability to dynamic external environments. The framework also incorporates True Cost Accounting (TCA) to evaluate socio-economic and environmental effects, supporting sustainable decision making. The article concludes that the integrated toolkit enhances the competitiveness, resilience, and sustainability of agricultural production by enabling data-driven, innovation-oriented, and EU-compliant strategies. It provides both theoretical contributions to the field of strategic management and practical guidelines for policymakers, agribusinesses, and regional clusters engaged in European integration and agricultural digitalisation.
Keywords: strategic management; agriculture; digital technologies; smart specialisation; integration; European economic area; clusters; data platforms; KPIs